Simultaneous determination of amlodipine and lisinopril dihydrate using fourth derivative spectroscopy - Nejres, Aws Maseer; Najem, Moath Abdallah (European Journal of Chemistry, 2023)
A new fast and simple selective method for the simultaneous determination of lisinopril dihydrate and amlodipine in combined drugs was developed using the fourth derivative spectrum method, based on the zero-crossing-point technique for the determination of compounds in drugs. The wavelength values for lisinopril dihydrate and amlodipine in solvent medium were found to be (203, 207, and 231 nm) and (215, 254, and 277 nm), respectively, with the average obeying Beer’s law in the range of lisinopril dihydrate 2.0 to 45.0 µg/mL and amlodipine 2.0 to 35.0 µg/mL. Lisinopril dihydrate has molar absorptivity regions (9227.76-11700.28 L/mol.cm, 203 nm), (15320.74-20795.59 L/mol.cm, 207 nm), and (2207.60-3311.40 L/mol.cm, 231 nm), while amlodipine (5886.72-10914.96 L/mol.cm, 215 nm), (5518.8-6418.16 L/mol.cm, 254 nm) and (1676.08-1921.36 L/mol.cm, 277 nm). The recovery rate of lisinopril dihydrate in the pharmaceutical dosage forms range was 95.13 to 102.60% and amlodipine 95.14 to 102.80%. The results of the relative error showed that the interferences did not affect the method of estimating these compounds. The proposed method has been successfully applied to estimate pharmaceutical dosage forms.